Assessment of the Antimicrobial Activity of Olive Leaf Extract Against Foodborne Bacterial Pathogens - Liu, Yanhong; McKeever, Lindsay C.; Malik, Nasir S. A. (Frontiers in Microbiology, 2017)
Olive leaf extract (OLE) has been used traditionally as a herbal supplement since it contains polyphenolic compounds with beneficial properties ranging from increasing energy levels, lowering blood pressure, and supporting the cardiovascular and immune systems. In addition to the beneficial effects on human health, OLE also has antimicrobial properties. The aim of this work was to investigate the antimicrobial effect of OLE against major foodborne pathogens, including Listeria monocytogenes, Escherichia coli O157:H7, and Salmonella Enteritidis. Our results demonstrated that at a concentration of 62.5 mg/ml, OLE almost completely inhibited the growth of these three pathogens. In addition, OLE also reduced cell motility in L. monocytogenes, which correlated with the absence of flagella as shown by scanning electron microscopy. Moreover, OLE inhibited biofilm formation in L. monocytogenes and S. Enteritidis. Taken together, OLE, as a natural product, has the potential to be used as an antimicrobial to control foodborne pathogens.